Total tumour volume as a prognostic factor in patients with resectable colorectal cancer liver metastases. Issue 3 (11th April 2020) - Tai, K.; Komatsu, S.; Sofue, K.; Kido, M.; Tanaka, M.; Kuramitsu, K.; Awazu, M.; Gon, H.; Tsugawa, D.; Yanagimoto, H.; Toyama, H.; Murakami, S.; et al.
Abstract : Background: Although total tumour volume (TTV) may have prognostic value for hepatic resection in certain solid cancers, its importance in colorectal liver metastases (CRLM) remains unexplored. This study investigated its prognostic value in patients with resectable CRLM. Method: This was a retrospective review of patients who underwent hepatic resection for CRLM between 2008 and 2017 in a single institution. TTV was measured from CT images using three‐dimensional construction software; cut‐off values were determined using receiver operating characteristic (ROC) curve analyses. Potential prognostic factors, overall survival (OS) and recurrence‐free survival (RFS) were determined using multivariable and Kaplan–Meier analyses. Results: Some 94 patients were included. TTV cut‐off values for OS and RFS were 100 and 10 ml respectively. Right colonic primary tumours, primary lymph node metastasis and bilobar liver metastasis were included in the multivariable analysis of OS; a TTV of 100 ml or above was independently associated with poorer OS (hazard ratio (HR) 6·34, 95 per cent c.i. 2·08 to 17·90; P = 0·002). Right colonic primary tumours and primary lymph node metastasis were included in the RFS analysis; a TTV of 10 ml or more independently predicted poorer RFS (HR 1·90, 1·12 to 3·57; P = 0·017). The 5‐year OS rate for a TTV of 100 ml or more was 41 per cent, compared with 67 per cent for a TTV below 100 ml ( P = 0·006). Corresponding RFS rates with TTV of 10 ml or more, or less than 10 ml, were 14 and 58 per cent respectively ( P = 0·009). A TTV of at least 100 ml conferred a higher rate of unresectable initial recurrences (12 of 15, 80 per cent) after initial hepatic resection. Conclusion: TTV was associated with RFS and OS after initial hepatic resection for CRLM; TTV of 100 ml or above was associated with a higher rate of unresectable recurrence. Abstract : This study investigated whether the total tumour volume (TTV) of colorectal liver metastases could predict patient survival after hepatic resection. Associations were identified between TTV and recurrence‐free survival, overall survival and unresectable recurrence after primary hepatic resection. TTV may represent a good basis for determining indications for hepatic resection. Total tumour volume predicts both overall and recurrence‐free survival Abstract : Antecedentes: Aunque el volumen total del tumor (total tumour volume, TTV) puede tener valor pronóstico tras la resección hepática (hepatic resection, HR) en algunas neoplasias sólidas, no se conoce su importancia en las metástasis hepáticas de cáncer colorrectal (colorectal liver metastases, CRLMs). Este estudio analizó el valor pronóstico del TTV en pacientes con CRLMs resecables. Métodos: Revisión retrospectiva de pacientes a los que se realizó una HR por CRLMs entre 2008 y 2017 en un solo centro. El TTV se estimó a partir de imágenes de tomografía computarizada utilizando un programa de reconstrucción 3D; se determinaron los valores de corte mediante un análisis de las características operativas del receptor. Se identificaron los posibles factores pronósticos y se calcularon la supervivencia global ( overall survival, OS) y la supervivencia libre de recidiva ( recurence‐free survival, RFS) mediante análisis multivariados y de Kaplan‐Meier. Resultados: Se incluyeron 94 pacientes. Los valores de corte del TTV para la OS y la RFS fueron de 100 mL y 10 mL, respectivamente. En el análisis multivariable para la OS, se incluyeron los tumores del colon derecho, las metástasis linfáticas primarias y la metástasis hepática bilobar; un TTV ≥ 100 mL se asoció de forma independiente con una peor OS (cociente de riesgos instantáneos, hazard ratio, HR, 6, 34, i.c. del 95% 2, 08‐17, 9; P = 0, 002). En el anáisis para la RFS, se incluyeron tumores primarios de colon derecho y las metástasis linfáticas primarias; un TTV ≥ 10 mL predijo de forma independiente una peor RFS (HR 1, 90, i.c. del 95% 1, 12‐3, 57; P = 0, 017). Las tasas de OS a los 5 años con TTVs ≥ 100 mL versus < 100 mL fueron del 41% versus 67% ( P = 0, 006); las tasas de RFS respecto a TTVs ≥ 10 mL versus < 10 mL fueron del 14% versus 58% ( P = 0, 009). Un TTV ≥ 100 mL conllevó una tasa más elevada (80%) de recidivas no resecables después de la HR inicial. Conclusión: El TTV se asoció con la RFS y la OS tras la HR por CRLMs; unos valores ≥ 100 mL conllevan una tasa más elevada de recidiva irresecable.